(untitled) (Research, Society and Development, 2022)
The objective of this research was to evaluate the attitudes and behaviors of dentists regarding the use of faceshield in the COVID-19 pandemic. The research was carried out through an online questionnaire consisting of 20 multiple choice questions about the use of this personal protective equipment by professionals working in the dental practice. Two hundred and eighty-nine dentists answered the survey. It was found that 56.4% believe that its use is essential in any procedure and 37.4% believe that it depends on the type of treatment performed or that it can be replaced by another device. Regarding its use during dental care, 36.7% do not use it continuously, only when there is aerosol formation, 10% indicated not using it, while 45.3% always use it. Regarding the interference in the quality of their work, 57.4% believe that the use of it interferes with the result and 37.7% do not. The most common problems during use were difficulty in viewing (56.1%), blurring (44.3%) and annoying (39.8%). A great demand of professionals had difficulties in finding a faceshield that would adapt perfectly, testing several (69.3% at least two types). Among the other pertinent aspects that were scored, a large percentage of professionals feel familiar with biosafety protocols in clinical routine, but only 32.5% understand that there is a need to wear an N95 mask or similar, surgical mask, goggles and faceshield. In conclusion, the faceshield has not been used by dentists in all daily procedures during clinical practice in the pandemic period.